2015
DOI: 10.5812/aapm.28844
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ketamine on Early Postoperative Cognitive Function After Orthopedic Surgery in Elderly Patients

Abstract: Background:Postoperative cognitive dysfunction (POCD) is a serious and frequent complication after surgery, especially in elderly patients. Ketamine is an N-methyl D-aspartic acid receptor antagonist with demonstrated neuroprotective effects. An intravenous bolus of a sub-anesthetic dose (0.5 mg/kg) of ketamine can reduce postoperative delirium (POD) and POCD after cardiac surgery. But, the influence of ketamine on early POCD after non-cardiac surgery is unclear.Objectives:The current study aimed to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 24 publications
(38 reference statements)
0
39
0
Order By: Relevance
“…Recent randomized, prospective trials, however, could not confirm the effectiveness of haloperidol prophylaxis to reduce incidence or length of delirium [71][72][73]. Ketamine was reported to reduce the incidence of POD in a single-center prospective study in cardiac surgery, whereas no effect was found upon a single dose of 0.5 mg/kg ketamine in a study involving 56 elderly orthopedic patients under general anesthesia [74]. Though lower plasma GABA level had a significant independent association with POD [75], a perioperative course of gabapentin produced only a clinically insignificant improvement in analgesia, but was associated with a higher incidence of sedation [76].…”
Section: Pharmacological Treatmentmentioning
confidence: 93%
“…Recent randomized, prospective trials, however, could not confirm the effectiveness of haloperidol prophylaxis to reduce incidence or length of delirium [71][72][73]. Ketamine was reported to reduce the incidence of POD in a single-center prospective study in cardiac surgery, whereas no effect was found upon a single dose of 0.5 mg/kg ketamine in a study involving 56 elderly orthopedic patients under general anesthesia [74]. Though lower plasma GABA level had a significant independent association with POD [75], a perioperative course of gabapentin produced only a clinically insignificant improvement in analgesia, but was associated with a higher incidence of sedation [76].…”
Section: Pharmacological Treatmentmentioning
confidence: 93%
“…The influence of ketamine on early postoperative cognitive function after orthopedic surgery under GA was studied in a RCT that enrolled 56 (> 60 years old) patients [28]. GA was maintained with propofol, rocuronium, desflurane and remifentanil.…”
Section: Anesthesia Exposure and Chronic Neurocognitive Disordersmentioning
confidence: 99%
“…Of these, 12 were further excluded (not adequately controlled [n = 3], inadequate intervention [n = 3], no outcome of interest [n = 3], no general anaesthesia [n = 3]) . Seven reports comparing the administration of intraoperative ketamine with no intervention (no drug or placebo) were included . Data from 1 trial reported in 2 separate publications were merged under a unique identification (Hudetz 2009) .…”
Section: Resultsmentioning
confidence: 99%
“…All trials were performed in a major surgery setting except one conducted in a mixed setting (major and minor orthopaedic procedures) . Surgical settings and surgery duration varied across trials.…”
Section: Resultsmentioning
confidence: 99%